1987
DOI: 10.1007/bf01310735
|View full text |Cite
|
Sign up to set email alerts
|

Studies on in vitro Interferon induction capacity and Interferon sensitivity of Simian Foamy viruses

Abstract: We demonstrate that Simian Foamy viruses (SFV) types 1, 2, 4 and 10 do not induce Interferon (IFN) production in mouse and primate (simian and human) cell lines, but that their cytopathogenic effect is blocked by this viral inhibitor. The mechanisms of action of IFN seems to be different from that of other Retroviridae. No trapping of virions appears in treated cells examined by ectron microscopy. Moreover, neither precursor nor mature virus particles were observed in infected cultures submitted to IFN treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…IFN partially abrogates reactivation of latent FV by PMA. The antiviral effects of interferons on FV replication in fully permissive cell types is well documented (27)(28)(29)(30) PMA (Fig. 5).…”
Section: Expression Of Pml-binding Domain Of Tas Does Not Induce Fv Rmentioning
confidence: 94%
See 1 more Smart Citation
“…IFN partially abrogates reactivation of latent FV by PMA. The antiviral effects of interferons on FV replication in fully permissive cell types is well documented (27)(28)(29)(30) PMA (Fig. 5).…”
Section: Expression Of Pml-binding Domain Of Tas Does Not Induce Fv Rmentioning
confidence: 94%
“…The effects of overexpressed or IFN-induced PML on FV replication are evident (27). However, FVs have apparently evolved a replication strategy that does not induce IFN (14,29). Therefore, the role of PML in FV biology remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune system sensing of FV infections is poorly characterized. A failure of FVs to induce type I interferon (IFN-I) was suggested by early studies using primate or human cell lines [73,74,75]. A very recent study by Rua and colleagues, however, demonstrates that FVs are efficiently sensed by primary human hematopoietic cells [76].…”
Section: Innate Sensing and Cellular Restriction Factors Of Fvsmentioning
confidence: 99%
“…Specifically, it was reported that ␥-IFN delayed the cultivation of FVs and, furthermore, that the likelihood of isolating FV from naturally infected host cells was strongly enhanced by the addition of antibodies to ␥-IFN to the culture medium (15). These findings point to the vulnerability of FV replication to the IFN system although FVs are not regarded as superb IFN inducers (51).…”
Section: Analysis Of Pfv Revertants and Pseudo-revertants In Gagmentioning
confidence: 99%
“…Early reports on the IFN-dependence of FV replication (50,51) were the rationale behind this experiment. Specifically, it was reported that ␥-IFN delayed the cultivation of FVs and, furthermore, that the likelihood of isolating FV from naturally infected host cells was strongly enhanced by the addition of antibodies to ␥-IFN to the culture medium (15).…”
Section: Analysis Of Pfv Revertants and Pseudo-revertants In Gagmentioning
confidence: 99%